2014
DOI: 10.1073/pnas.1323014111
|View full text |Cite
|
Sign up to set email alerts
|

Neural sensitivity to eudaimonic and hedonic rewards differentially predict adolescent depressive symptoms over time

Abstract: The pursuit of happiness and reward is an impetus for everyday human behavior and the basis of well-being. Although optimal well-being may be achieved through eudaimonic activities (e.g., meaning and purpose), individuals tend to orient toward hedonic activities (e.g., pleasure seeking), potentially placing them at risk for ill-being. We implemented a longitudinal study and followed adolescents over 1 y to examine whether neural sensitivity to eudaimonic (e.g., prosocial decisions) and hedonic (e.g., selfish r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
129
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(142 citation statements)
references
References 39 publications
8
129
1
Order By: Relevance
“…Instead, it offers an immediate symbolic benefit (and, consequently, eudaimonic reward) for resisting temptation: feeling like a high-status and respect-worthy person right now because one is acting in accordance with important values shared with one's peers. Previous neuroscientific research shows that adolescents are especially likely to experience an immediate feeling of reward, comparable to what one feels in response to positive hedonic experiences, when they are made to feel socially valuable (19). We suggest that the immediacy of this eudaimonic reward gives it the emotional and motivational power to compete effectively with the anticipated hedonic reward of succumbing to temptation (19).…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Instead, it offers an immediate symbolic benefit (and, consequently, eudaimonic reward) for resisting temptation: feeling like a high-status and respect-worthy person right now because one is acting in accordance with important values shared with one's peers. Previous neuroscientific research shows that adolescents are especially likely to experience an immediate feeling of reward, comparable to what one feels in response to positive hedonic experiences, when they are made to feel socially valuable (19). We suggest that the immediacy of this eudaimonic reward gives it the emotional and motivational power to compete effectively with the anticipated hedonic reward of succumbing to temptation (19).…”
Section: Discussionmentioning
confidence: 65%
“…Previous neuroscientific research shows that adolescents are especially likely to experience an immediate feeling of reward, comparable to what one feels in response to positive hedonic experiences, when they are made to feel socially valuable (19). We suggest that the immediacy of this eudaimonic reward gives it the emotional and motivational power to compete effectively with the anticipated hedonic reward of succumbing to temptation (19). This general approach might be effective at any age if the relevant behavior can be construed in terms appropriate to the target audience.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although abnormal approach-avoidance behavior is common to all three disorders, depression and anxiety are associated with overactive avoidance of certain social and emotional situations (Trew, 2011;Caouette and Guyer, 2014), whereas CUDs may be associated with overactive approach of cannabis cues . Moreover, SUDs including CUDs and depression are both characterized by low positive affect (anhedonia) and abnormal reward responsiveness within various fronto-limbic brain areas (Koob and Volkow, 2010;Hatzigiakoumis et al, 2011;Elman et al, 2013;Morgan et al, 2013;Telzer et al, 2014). Interestingly, a recent PET study among 14 heavy cannabis users showed a link between anhedonia and reduced dopamine transmission in the striatum (Bloomfield et al, 2014).…”
Section: Embracing Comorbidity As a Toolmentioning
confidence: 99%